Perinatal Outcomes after Short versus Prolonged Indomethacin for Tocolysis in Women with Preterm Labor - Dutta, Eryn H.; Behnia, Faranak; Harirah, Hassan; Costantine, Maged; Saade, George (American Journal of Perinatology, 2016)
Objective Indomethacin tocolysis is generally limited to 48 hours. Indomethacin has been administered for longer durations to prolong gestation in extreme prematurity. Our aim is to compare perinatal outcomes after a prolonged course, > 48 hours versus ≤  48 hours in preterm labor.Methods A retrospective chart review of women admitted with preterm labor < 32 weeks gestation who received indomethacin for tocolysis. The primary maternal outcome was latency from admission until delivery. The primary neonatal outcome was a composite of severe neonatal morbidities.Results A total of 73 women were included: 32 (43.8%) received indomethacin for > 48 hours (prolonged) and 41 (56.2%) for ≤ 48 hours (standard). Prolonged group started on indomethacin at an earlier gestational age compared with standard group (23.9 [23.1–27.3] vs. 25.7 [23.8–28.5] weeks, p = 0.03). Latency from admission until delivery was longer in the prolonged group versus the standard group (1.8 [1.1–3] vs. 0.4 [0.1–0.8] weeks, p < 0.001). Prolonged use was not associated with increased risk of the composite neonatal outcome; however, there was a trend for more necrotizing enterocolitis.Conclusion A prolonged course of indomethacin may be an option for women with preterm labor at risk of extreme prematurity; it may also be associated with higher risks of some adverse neonatal outcomes.
Keywords: preterm labor; indomethacin; tocolysis; neonatal outcomes; necrotizing enterocolitis